The survey of learning experience of pediatric injection among registered nurses and nursing students using a design thinking approach - Chanita Tantacharoenrat; Monamorn Precharattana (Wolters Kluwer Medknow Publications, 2024)
INTRODUCTION: Pediatric injection is an essential skill of nursing. The survey of the learner's experience during the learning process helps identify problems and leads to improvement. We here applied a three-phrase design thinking framework. The study aims to investigate (1) the registered nurses' experience in learning injection technique, (2) the nursing students' experience in learning injection, and (3) the cause of problems and to propose (4) a learning material that will be used to solve the encountered problems. MATERIALS AND METHODS: A cross-sectional study was applied. The study employed convenience sampling. Registered nurses from a tertiary hospital in Bangkok, Thailand, and fourth-year nursing students from a nursing school in Bangkok, Thailand, were selected. The data collecting tools contain a personal information form and the experience of injection learning. The inferential and descriptive statistics was used to analyze the data. RESULTS: The results show that the major issues of injection learning include selecting the correct site for injection and determining the needle length and injection angle and contamination. CONCLUSIONS: Therefore, teaching materials for the anatomy of the injection area and the technique to determine the correct size and depth of injection are needed.